Genetic and Clinical Analyses of 13 Chinese Families With Cystine Urolithiasis and Identification of 15 Novel Pathogenic Variants in SLC3A1 and SLC7A9 - Li, Chuangye; Yang, Yongjia; Zheng, Yu; Shen, Fang; Liu, Li; Li, Yanfang; Li, Liping; Zhao, Yaowang (Frontiers in Genetics, 2020)
Abstract Background: Cystinuria is a rare genetic disorder characterized by defective renal reabsorption of cystine, ornithine, arginine, and lysine. The increased urinary excretion of cystine results in the development of cystine urolithiasis (CU). The mutated SLC3A1 and SLC7A9 genes are the cause of CU, a global disorder. Its frequency and mutation spectrum vary between different populations. In Asia, the data for CU are limited. Method: Urinary stones were collected from patients of a single center over a five-year period and analyzed via Fourier transform infrared spectroscopy. Genomic DNA was isolated from 13 patients with CU and their parents and from 26 controls affected by calcium oxalate dihydrate stones. The coding regions and the exon–intron boundaries of SLC3A1 and SLC7A9 were subjected to PCR amplification and then sequenced via traditional Sanger sequencing. Genetic variants were functionally annotated using the InterVar, ClinVar, gnom AD, and HGMD databases. Results: From the 232 samples of urinary stones, we identified 13 patients with CU (10 males and 3 females). The onset age was from 7 months to 9 years. The CU stones varied from 0.26 cm3 to 18.67 cm3. Sanger sequencing detected a total of 14 SLC3A1 (nine were novel) and 10 SLC7A9 (six were novel) rare variants from the 13 CU families. All variants, including 15 novel variants, were pathogenic, disease-causing, or damaging. Conclusion: All 13 pediatric CU families harbored SLC3A1 or/and SLC7A9 rare variants. A total of 15 novel pathogenic variants in SLC3A1 and SLC7A9 were identified. This study expanded the known mutational spectrum of CU in the Chinese population.